2016
DOI: 10.5021/ad.2016.28.2.222
|View full text |Cite
|
Sign up to set email alerts
|

The MARCOPOLO Study of Ustekinumab Utilization and Efficacy in a Real-World Setting: Treatment of Patients with Plaque Psoriasis in Asia-Pacific Countries

Abstract: BackgroundUstekinumab is a fully human monoclonal antibody approved for the treatment of chronic moderate-to-severe plaque psoriasis in adults. However, factors including efficacy, tolerability, ease of use, and cost burden may affect ustekinumab utilization. Noncompliance may, in turn, affect treatment response.ObjectiveTo evaluate ustekinumab utilization in the real-world setting in Asia-Pacific countries.MethodsIn this phase 4 observational study conducted in Indonesia, Malaysia, Singapore, Korea, and Taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…In contrast, early studies of anti-TNF biologics in Asian populations produced variable efficacy results, possibly due to small sample size. 29 More recent studies with agents targeting IL-12/23, IL-23, or IL-17 have demonstrated efficacy results in Asian patients that are generally comparable with those reported in non-Asian patients, 4,[13][14][15][16][17][18][19] as demonstrated in this post-hoc analysis.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In contrast, early studies of anti-TNF biologics in Asian populations produced variable efficacy results, possibly due to small sample size. 29 More recent studies with agents targeting IL-12/23, IL-23, or IL-17 have demonstrated efficacy results in Asian patients that are generally comparable with those reported in non-Asian patients, 4,[13][14][15][16][17][18][19] as demonstrated in this post-hoc analysis.…”
Section: Discussionsupporting
confidence: 72%
“…Studies of anti‐tumor necrosis factor (TNF) agents in Asian patients have been reported, but many of these studies are smaller and later in the development cycle of the agent than studies in populations of mixed race . Substantial numbers of Asian patients were included in the pivotal studies of agents targeting interleukin (IL)‐12/23, IL‐23, and IL‐17, allowing for subanalyses of the Asian populations in these studies . Separate studies of these agents have also been conducted specifically in Asian countries …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical outcomes (mainly PASI) were reported in 75% of prospective studies [27, 39, 47-53], in about 50% of prospective registries [20, 24, 54-61] and retrospective studies [29, 30, 32, 34, 37, 62-70], and in no retrospective administrative databases/claims. Drug survival of biological therapies was reported in over 60% of prospective registries [14, 20, 21, 24, 25, 31, 54, 57, 71-74], retrospective studies [18, 19, 22, 23, 26, 29, 30, 32, 34, 37, 38, 68, 70, 75-77] and administrative databases/claims [28, 35, 36, 40-42, 46], and less frequently (33%) in prospective studies [27, 33, 52, 78].…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of patients who discontinued biological therapies within the end of the follow-up period was reported in 90% of retrospective administrative databases/claims [28, 35, 36, 40-45] and in about 60% of other study designs. Compliance with biological therapies was rarely considered in these effectiveness studies [15, 43, 45, 53]. …”
Section: Resultsmentioning
confidence: 99%